Analisis Dan Perancangan Sistem Informasi Layanan Pengadaan Barang Dan Jasa Berbasis Web Pada Polda Jambi - Marlinda, Tina; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2020)
Problems that occur in the procurement of goods and services in the Polda Jambi are among other things thelegislation regarding procurement of goods and services which is always changing which is always followedby changes in supporting documents and procedures and provisions in the auction, resulting in differentways the viewpoints of each section involved in preparing procurement documents, making work contractsalso making the minutes of handover of the results of the procurement of goods / services, also the absence ofspecial media that is used as a source of information and technical guidance in improving the ability of theactors in the procurement of goods and services in Polda Jambi. The purpose of this study includes analyzingand designing a service system for the procurement of goods and services in the Polda Jambi which can laterbe a solution to the problem of procurement of goods and services used today. This study uses UML tools,including use case diagrams, activity diagrams, and class diagrams. In this research, a prototype of a WebBased Goods and Services Procurement Information System Service in Polda Jambi makes it easy forproviders of goods and services to obtain information about the provisions that apply to cooperate with thePolda Jambi in the supply of goods and services. The suggestion in this research is that the design of thissystem needs to be developed so that it can really be applied to the Polda Jambi, and further research can besupplemented by a data security system